The Influence of Design on Electrical Performance of AlGaN/GaN Lateral Schottky Barrier Diodes for Energy-Efficient Power Applications - Egor Polyntsev (MDPI AG, 2021)
In this paper, lateral AlGaN/GaN Schottky barrier diodes are investigated in terms of anode construction and diode structure. An original GaN Schottky diode manufacturing-process flow was developed. A set of experiments was carried out to verify dependences between electrical parameters of the diode, such as reverse and forward currents, ON-state voltage, forward voltage and capacitance, anode-to-cathode distance, length of field plate, anode length, Schottky contact material, subanode recess depth, and epitaxial structure type. It was found that diodes of SiN/Al0.23Ga0.77N/GaN epi structure with Ni-based anodes demonstrated two orders of magnitude lower reverse currents than diodes with GaN/Al0.25Ga0.75N/GaN epitaxial structure. Diodes with Ni-based anodes demonstrated lower VON and higher IF compared with diodes with Pt-based anodes. As a result of these investigations, an optimal set of parameters was selected, providing the following electrical characteristics: VON = 0.6 (at IF = 1 mA/mm), forward voltage of the diode VF = 1.6 V (at IF = 100 mA/mm), maximum reverse voltage VR = 300 V, reverse leakage current IR = 0.04 μA/mm (at VR = −200 V), and total capacitance C = 3.6 pF/mm (at f = 1 MHz and 0 V DC bias). Obtained electrical characteristics of the lateral Schottky barrier diode demonstrate great potential for use in energy-efficient power applications, such as 5G multiband and multistandard wireless base stations.